Coyuntura Económica - Martínez Sandoval, Avelino; Aponte , Guillermo; Sánchez Rengifo, Holmes; Carrillo-Rodríguez, Lilian Andrea; Vázquez Olave, Martha; Ángel Giraldo, Leidy (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2007)
Coyuntura económica